PENGARUH PEMBERIAN EKSTRAK DAUN BELALAI GAJAH TERHADAP KADAR MALONDIALDEHID DAN SUPEROKSIDA DISMUTASE PADA TIKUS DENGAN AKTIVITAS TINGGI - Felix, Jesslyn; Suyono, Tan; Chiuman, Linda (Lantanida Journal, 2023)
Clinacanthus nutans Lindau is known as the elephant trunk leaf which belongs to the Acanthaceae family. C. nutans can act as an antioxidant by reducing free radicals from the mitochondrial electron transport chain in the cell membrane. In this study, elephant trunk leaves will be studied regarding their content and antioxidant activity and their association with free radicals/Reactive Oxygen Species (ROS), which are compounds that are highly reactive. ROS can cause damage to cell integrity and functional cell disruption. Free radical reduction prevents lipid oxidation, which then reduces malondialdehyde (MDA) levels. By potentiating the antioxidant properties of Superoxide Dismutase (SOD) and reducing lipid peroxidation, C. nutans can reduce oxidative stress. The purpose of this study was to evaluate the effect of elephant trunk leaf extract on malondialdehyde and superoxide dismutase levels in rats with high activity. The research method used was laboratory experimental research with a Randomized Posttest Only with Control Group Design. In this study, 25 male white rats of the Wistar strain were divided into 5 groups: normal, negative control, and treatment I, II, III which were given elephant trunk leaf extract at successive doses of 50, 300, and 2000 mg/kg BW ( Weight). and high activity for 14 days. MDA measurements using a spectrophotometer and SOD using calorimetry were carried out after 14 days. The results showed that elephant trunk leaf extract reduced MDA levels and increased SOD activity in the blood plasma of rats induced by high activity (P value <0.05).